2023
DOI: 10.1182/blood.2022017074
|View full text |Cite
|
Sign up to set email alerts
|

Factor XII contributes to thrombotic complications and vaso-occlusion in sickle cell disease

Abstract: A hypercoagulable state, chronic inflammation, and increased risk of venous thrombosis and stroke are prominent features in patients with sickle cell disease (SCD). Coagulation factor XII (FXII) triggers activation of the contact system that is known to be involved in both thrombosis and inflammation, but not in physiological hemostasis. Therefore, we investigated whether FXII contributes to the prothrombotic and inflammatory complications associated with SCD. We found that when compared to healthy controls, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Finally, a recent study by Sparkenbaugh et al explored the contribution of FXII to thrombotic complications in individuals with SCD. 46 This study demonstrated that FXIIa contributes to the activation of the intrinsic and inflammatory pathways in SCD patients. Sparkenbaugh et al reported highly significant correlations between FXIIa:C1 and FXIa: C1 with FIXa:AT complexes and also a significant correlation between plasma levels of PKa:C1 and FIXa:AT complexes.…”
Section: Direct Activation Of Fix By Pka Results In Thrombin Generati...mentioning
confidence: 65%
See 1 more Smart Citation
“…Finally, a recent study by Sparkenbaugh et al explored the contribution of FXII to thrombotic complications in individuals with SCD. 46 This study demonstrated that FXIIa contributes to the activation of the intrinsic and inflammatory pathways in SCD patients. Sparkenbaugh et al reported highly significant correlations between FXIIa:C1 and FXIa: C1 with FIXa:AT complexes and also a significant correlation between plasma levels of PKa:C1 and FIXa:AT complexes.…”
Section: Direct Activation Of Fix By Pka Results In Thrombin Generati...mentioning
confidence: 65%
“…These data reflect FXIIa activation of both FXI and PK in SCD patients, and furthermore suggest that activation of FIX is mediated by both FXIa and, in part, by PKa. 46 However, as in the previously mentioned study by Henderson et al, further work is needed to conclude that the correlation between PKa:C1 levels and FIXa:AT levels is due to activation of FIX by PKa in these patients. 45…”
Section: Direct Activation Of Fix By Pka Results In Thrombin Generati...mentioning
confidence: 76%
“…Meanwhile, negatively charged hemostatic materials can rapidly activate endogenous coagulation pathways by activating FXII [ 45 , 46 , 54 ]. The quantitative analysis of HPA-5 interactions with FXII indicated a reduced content of the FXII factor in the HPA-5 group (123.77 ng/mL) compared with the blank group (435.25 ng/mL).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, soluble PLAUR is also a biomarker of disease severity in other conditions associated with immunothrombosis and alveolar damage such as sepsis ( 25 , 26 ). Another pathway that could link increased PLAUR levels with coagulation activation is the association of this molecule with factor XII and neutrophil activation, which has been demonstrated in wound healing ( 27 ) and sickle cell disease ( 28 ).…”
Section: Discussionmentioning
confidence: 99%